Morphological Predictive Features on Spectral-Domain Optical Coherence Tomography for Visual Outcomes in Neovascular Age-Related Macular Degeneration Treated with Ranibizumab. (26th June 2018) - Azar, Georges; Wolff, Benjamin; De Bats, Flore; Halfon, Jeremie; Streho, Mate; Tick, Sarah; Castelnovo, Laurent; Michel, Guillaume; Masse, Helene; Vasseur, Vivien; Sahyoun, Marwan; Mauget-Faÿsse, Martine
Abstract : Purpose . To identify spectral-domain optical coherence tomography (SD-OCT) predictive morphological features for the outcome of Ranibizumab therapy for neovascular age-related macular degeneration (AMD). Methods . This is a retrospective multicentric study that involved 64 eyes with naïve AMD. Patients who received three monthly intravitreal injections of Ranibizumab were stratified into (1) "responders" [≥ 5 letters gain on Early Treatment Diabetic Retinopathy Study (ETDRS) scale] and (2) "nonresponders" (< 5 letters gain). Best-corrected visual acuity (BCVA) and SD-OCT morphological features were compared at baseline and one month after three consecutive injections of Ranibizumab. Univariate and multivariate analyses were carried out to correlate these morphological features with the change in BCVA. Results . Among the 64 patients enrolled, 40 (62.5%) were "responders" and 24 (37.5%) "nonresponders". Age, sex, and BCVA were comparable between both groups. A multivariate correlational analysis found that subfoveal choroidal thickness (SFCT) and the presence of pigment epithelial detachment (PED) > 250 μ m at baseline were two independent prognostic indicators of final BCVA. No other SD-OCT morphological studied features seem to affect final BCVA after Ranibizumab treatment. Conclusion . SFCT and the presence of PED > 250 μ m are two significant biomarkers that may predict improvement after Ranibizumab therapy for AMD. These markers may guide ophthalmologists' treatment decision under financial constraints and limited time.